Pengaruh kualitas sumber daya manusia, kesempatan kerja, dan pertumbuhan ekonomi terhadap jumlah penduduk miskin di Kabupaten Sarolangun - Septina Sovia; Junaidi Junaidi; Etik Umiyati (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
The study aims to analyze the influence of the quality of human resources, employment opportunities and economic growth on the number of poor people in Sarolangun District. The data used in this study are secondary data, from 2002 to 2012. Data is sourced from the Central Bureau of Statistics of Jambi Province, the Sarolangun Regency Central Bureau of Statistics and the Regional Planning and Development Agency of Sarolangun Regency. The analysis tool used is a multiple linear regression method. The results showed that simultaneously the quality of human resources, employment opportunities, and economic growth had a significant effect on the number of poor people in Sarolangun District. Partially. employment and economic growth have a significant effect while the quality of human resources has no significant effect on the number of poor people